THE FORMATION OF WORLD HISTORY THROUGH THE EYES AND EXPERIENCES OF EXPLORERS - Kumar, Jagdish (International Journal of Research -GRANTHAALAYAH, 2025)
The assertion that there were surprising similarities between the West and more advanced regions of Asia during the period of 1800–1830, and that the Industrial Revolution was the key transformation that distinguished Europe from Asia, is a core argument among multicultural historians like Kenneth Pomeranz, Bin Wong, Jack Goldstone, John Hobson, and Peer Vries. These scholars approach the rise of the West, primarily by examining the emergence of mechanized industry, the utilization of inorganic energy sources, and the ability to surpass Malthusian constraints on growth. However, a central point of my book, The Uniqueness of Western Civilization, is that the divergence of the West cannot be separated from its developmental history, which includes the Greek and Roman assemblies of citizens, the parliaments, municipal communes, universities, and estates of the medieval period, as well as the reading societies, representative institutions, journals, and newspapers that emerged during the Enlightenment. The establishment of liberal democratic institutions is a key aspect of what makes the West unique and contributes to its rise to prominence. Additionally, our argument emphasizes that it is not any specific renaissance, revolution, or liberal institution that defines the West, but rather its significantly higher levels of achievement across various intellectual and artistic fields.